THE EFFECT OF REPLACEMENT COMMERCIAL RAW WITH BREAD WASTE ON THE PHYSICAL COMPOSITION OF CARCASES OF KAMPUNG UNGGUL BALITNAK (KUB) CHICKENS - N., Wahyuni; Ariana, I N. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
The aim of this study is was to determine how the effect of replacing commercial rations with bread waste on the physical composition of the carcass of Kampung Unggul Balitnak (KUB) chickens. This research was conducted at a farm located on Banjar Ulun Uma Badung, Gulingan Village, Mengwi District, Badung Regency for 8 weeks.The research design used was a completely randomized design (CRD) which consisted of 3 treatments and 5 replications where each replication contained 2 KUB chickens with one week of age and homogeneous weight. The three treatments were Balitnak Superior Village Chicken (KUB) which was given a commercial ration treatment without bread waste (P0), Balitnak Superior Village Chicken (KUB) which was given 75% commercial ration + 25% bread waste (P1), and Free-range Chicken. Unggul Balitnak (KUB) treated with 50% commercial ration + 50% bread waste (P2). The variables observed were slaughter weight, carcass weight and carcass percentage as well as the percentage of carcass physical composition which included bone, meat, and fat.The results showed that the effect of replacing commercial rations with bread waste at the level of 25% and 50% had a significant (P<0.05) effect on slaughter weight and carcass weight, while the percentage of carcass and the percentage of carcass physical composition of bone, meat and fat did not significantly different (P>0.05). From the results of this study, it can be concluded that the replacement of commercial rations with bread waste at the level of 25% and 50% gave the same results on the slaughter weight and carcass weight as well as the physical composition of the carcass of Kampung Unggul Balitnak (KUB). Key words: Balitnak Superior Village Chicken (KUB), bread waste flour, carcass physical composition.